ANALISIS ISI LAMBUNG IKAN LAIS JANGGUT (Kryptopterus limpok, Bleeker 1852) DI SUNGAI TAPUNG HILIR PROPINSI RIAU - Ravki Adiyanda; Roza elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Research on the analysis of stomach content of Lais janggut fish (Kryptopterus limpok, Bleeker 1852) from Tapung River was conducted from December 2012 to February 2013. Fish samples had been taken from the Tapung Hilir river which was divided into three stations: Salembakan Palas, Flamboyan, and Kota Garo. The purposes of this study were to determine the types of food of Lais janggut fish covering the main food, food supplements and additional food at the three stations. The analysis used was the index of preponderance. The index of preponderance was used to analyze the stomach content. It was indicated that the main food and food supplements of Lais janggut fish in Salembakan Palas station consist of Puntius sp (89.3%) and litter (1.1%), arthropods (1.2%), animal debris (8.2%). The Lais janggut fish from Flamboyan station has main food of Puntius sp (84.1%), food supplements in the form of litter (4.5%) and animal debris (8.2%) and additional food such as arthropods (3.2%). Furthermore Lais janggut fish from Kota Garo station has main food debris in the form of animals (45%) and Puntius sp (43.9%), supplementary food such as fish Puntius sp (37%) and food supplements in the form of litter (6.0%) and Arthropods (4.7%). The main food, food supplements, and additional food of Janggut lais fis in Tapung Hilir river were Puntius sp, litter, animal debris, and arthropods respectively.